Legal aspects of remote work in modern realities - Nazarchuk, Oksana (Actual problems of law (Aktual’ni problemi pravoznavstva), 2023)
The article defines the features of remote work in modern realities. The mechanism for the implementation of remote work is a new challenge of the time, so the study of this form of employment is quite relevant in relation to the context of regulating labor relations in the context of the emergence of crisis conditions in the state and society, as well as taking into account the rapid development of innovative technologies and digitalization. One of the main advantages is the opportunity to continue to work and maintain the economic balance and competitiveness of our country. Attention is drawn to the fact that remote work requires not only the improvement of digital experience in the labor industry, but also additional protection of the labor rights of each person - this leads to problems and forms vectors for further research. It is characterized that remote work creates risks of reducing the social protection and social security of workers, which is unacceptable, because the features of modern labor demonstrate a change in the traditional limits of labor, the role of the individual qualities and competencies of the employee is increasing. The international experience of remote work in such countries as Great Britain, Belgium, Italy has been studied. Remote work at the legislative level has somewhat eased the situation, but in some cases has led to additional questions for both employees and employers. Workers need to receive special training for the transition to remote work, as there is a need to make sure that such a person can effectively carry out his work in this format. It is considered that remote work during martial law reflects the dual aspects of the subjects of labor law. Problems are identified: protection of confidential information, safety of the employee and his family members and the equipment entrusted to him, accounting of working time and rest time of the employee; application of disciplinary measures for absenteeism.